“Meraba” Pornografi di Ruang Kelas - Gani, Rita (Mediator, 2007)
Controversies spark everywhere when Playboy, an American franchise adult magazine, appeared in the market. Although Indonesians have experienced some important social transformations, such controversies marked the proof that there are still many conservatives among Indonesians who object a man-magazine like Playboy. The heart of controversies against Playboy lies in the fact that Playboy openly brought pornography among members of society. Such issue also become the heart of discussions among communication students who participate in Mass Media Ethics class. By openly discussing such matters, students could understand the controversies from range of perspectives: legal matters, social aspects, psychological dimensions, and so on.